True colors the real life of the art world - Haden-Guest, Anthony
Covers a period during which the prevailing artistic fashion ahs shifted as frequently as the focus of the Whitney Biennial, when art and money, talent and celebrity have often been confused. During this period, figures such as Julian Schnabel, Jeff Koons, and Keith Haring have crossed over from the rarefield world of high art into popular culture; and art dealers, like Hollywood power agents, have often claimed as much attention as those they represented. Anthony Haden-Guest has moved within this world, and known the players. He delivers here an authoritative and deliciously inside account.